Emission Constrained Economic Dispatch Using Moth Flame Optimization and Bat Hybrid Algorithm - Ruta, Wilbert; Saulo, Michael; Odero, Nicodemus Abungu (International Journal of Engineering Research and Technology, 2018)
This paper presents the application of a novel Moth flame optimization and Bat hybrid algorithm in the area of emission constrained economic dispatch with the main goal of minimizing the total cost of electric generation while using thermal power plants with the considering of emissions reduction. This area is crucial due to rise of air pollution caused by greenhouse gases from thermal power plants and manufacturing industries, also the cost of generating electric power using thermal power plants is at elevated level which turns the electric energy to be expensive. The multi-objective economic dispatch with the consideration of emission was converted into single objective problem by using the price penalty factor method while the IEEE-30 bus test system was used for implementing the study. The results of Moth flame optimization and Bat hybrid algorithm were compared with other methods reported in the literature and found to be promising in terms of reduction of total cost of electric generation and greenhouse gases emissions from thermal power plants.
Keywords: Economic dispatch; Emission dispatch; Exploitation; Exploration; Multi-objective optimization; Price penalty factor